Competency Evolution: A Framework for Construction Project Managers: Evolusi Kompetensi: Kerangka Kerja untuk Manajer Proyek Konstruksi - Rostiyanti, Susy F.; Hansen, Seng; Vermatasari, Riri (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2024)
The effective execution of a construction project heavily relies on a diverse set of human resources possessing various competencies. Competency is a multifaceted concept with varied interpretations depending on its application and development. In this diverse landscape, competencies are commonly understood to encompass attributes such as knowledge, skills, and abilities. These competencies also feature distinct transferable qualities within intrapersonal and interpersonal competencies. This study delves into the crucial role of competencies in managing construction projects efficiently, emphasizing the three primary components. Employing a Systematic Literature Review, the study aims to uncover the nuanced aspects influencing project manager competencies. The primary objective is to unravel the competencies empowering project managers to successfully navigate construction projects. The findings highlight leadership as the paramount skill competency and underscore the importance of responsibility as a key attitude competency. Additionally, the study introduces a framework delineating the evolutionary progression of project manager competencies from intrapersonal to interpersonal over time. This framework serves as a valuable resource for project management professionals seeking to enhance their competencies and effectively address the dynamic challenges inherent in construction projects.